1995
DOI: 10.4141/cjas95-030
|View full text |Cite
|
Sign up to set email alerts
|

The effect of feed restriction and of a β-adrenergic agonist on plasma melatonin concentrations in domestic pigs

Abstract: S. 1995. The effect of feed restriction and of a 0-adrenergic agonist on plasma melatonin concentrations in domestic pigs. Can. J. Anim. . The objective of the present study was to determine the effect of feed restriction and a p-adrenergic agonist (isoproterenol)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…The most likely explanation of the differences in the effects of dobutamine and isoproterenol is that the dose of dobutamine used was too low to stimulate effectively P-adrenergic receptors in the pineal gland, because the increase in number of heart beats was lower after administration of dobutamine than after isoproterenol (data not shown). The increased level of plasma melatonin during the night and the next day was noted by Peacock et al [1995] after administration of very high doses (0.5mgkg body weight) of isoproterenol at 2000 and 2100 hr in feed-restricted pigs, but not in pigs receiving a normal diet.…”
Section: Discussionmentioning
confidence: 96%
“…The most likely explanation of the differences in the effects of dobutamine and isoproterenol is that the dose of dobutamine used was too low to stimulate effectively P-adrenergic receptors in the pineal gland, because the increase in number of heart beats was lower after administration of dobutamine than after isoproterenol (data not shown). The increased level of plasma melatonin during the night and the next day was noted by Peacock et al [1995] after administration of very high doses (0.5mgkg body weight) of isoproterenol at 2000 and 2100 hr in feed-restricted pigs, but not in pigs receiving a normal diet.…”
Section: Discussionmentioning
confidence: 96%
“…However, even in studies where a nocturnal peak was observed, not all pigs exhibited elevated levels during the scotophase. Therefore, Peacock et al [1995] concluded that “at least some pigs fail, under circumstances that remain unclear, to secrete melatonin”. Our present study may provide another explanation for the inconsistency in circadian variation of melatonin in pigs.…”
Section: Discussionmentioning
confidence: 99%
“…None of these are a suitable model for studies of human digestive processes. The pig, a large monogastric, omnivorous animal, was recently introduced, as a model for studies of interaction between melatonin and the GIT [Peacock et al, 1995;Ayles et al, 1996;Bubenik et al, 19961. In order to investigate the previously described protective effect of melatonin on the incidence of GU, two studies were performed. In the first one, ulcer scores and levels of melatonin in plasma and GIT tissues were determined after 4 weeks of dietary supple-mental unit.…”
Section: Introductionmentioning
confidence: 99%